Mapping the Brightness of Ganymede's Ultraviolet Aurora Using Hubble Space Telescope Observations. Issue 6 (15th June 2022) - Marzok, A.; Schlegel, S.; Saur, J.; Roth, L.; Grodent, D.; Strobel, D. F.; Retherford, K. D.
Abstract: We analyze Hubble Space Telescope observations of Ganymede made with the Space Telescope Imaging Spectrograph between 1998 and 2017 to generate a brightness map of Ganymede's oxygen emission at 1, 356 Å. Our Mercator projected map demonstrates that the brightness along Ganymede's northern and southern auroral ovals strongly varies with longitude. To quantify this variation around Ganymede, we investigate the brightness averaged over 36°‐wide longitude corridors centered around the sub‐Jovian (0° W), leading (90° W), anti‐Jovian (180° W), and trailing (270° W) central longitudes. In the northern hemisphere, the brightness of the auroral oval is 3.7 ± 0.4 times lower in the sub‐Jovian and anti‐Jovian corridors compared to the trailing and leading corridors. The southern oval is overall brighter than the northern oval, and only 2.5 ± 0.2 times fainter on the sub‐ and anti‐Jovian corridors compared to the trailing and leading corridors. This demonstrates that Ganymede's auroral ovals are strongly structured in auroral crescents on the leading side (plasma downstream side) and on the trailing side (plasma upstream side). We also find that the brightness is not symmetric with respect to the 270° meridian, but shifted by ∼20° towards the Jovian‐facing hemisphere. Our map will be useful for subsequent studies to understand the processes that generate the aurora in Ganymede's non‐rotationally driven, sub‐Alfvénic magnetosphere. Plain Language Summary: Northern lights often illuminate the night sky in a shimmering green or red tone at high geographic latitudes. This emission, scientifically referred to as aurora, is a result of electrically charged particles that move along Earth's magnetic field lines and interact with its atmosphere to produce auroral emission. Apart from the Earth, multiple other planets in our solar system also exhibit auroral emission. By characterizing the brightness and structure of these lights, we are therefore able to deduce insights about a planet's atmosphere, magnetic field and the physical processes occurring along the field lines from afar. In this work, we used observations from the Hubble Space Telescope to analyze the auroral emission of Jupiter's largest moon Ganymede. We combined multiple images of Ganymede to create the first complete map that displays the auroral brightness. Our map revealed that the emission on Ganymede's auroral ovals varies strongly in brightness with divisions into two distinct bright and faint regions. They resemble two auroral crescents in the north and south respectively, and demonstrate the uniqueness of Ganymede's aurora in comparison with the auroral ovals of other planets in the solar system. Key Points: Brightness map of Ganymede's ultraviolet auroral emission has been constructed based on Hubble Space Telescope observations from 1998 to 2017 Auroral ovals are structured in upstream and downstream "crescents" Brightness on sub‐Jovian and anti‐Jovian side is strongly reduced by a factor of 3–4 compared to upstream and downstream side